ANALYSIS OF FACTORS AFFECTING INDONESIAN CANE MOLASSES EXPORT VOLUME - Alifio Aradea Putranto; Made Kembar Sri Budhi (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Cane molasses is a by-product of sugarcane processing that can no longer be crystallized and still contains sugar and non-sugar (organic) materials. Between 2000 and 2023, molasses production in Indonesia has shown continuous growth, with an average export value of USD 56.3 million. This study aims to examine the effects of export price, sugarcane production, sugarcane plantation area, and inflation rate on the export volume of Indonesian cane molasses during the 2000–2023 period. This research employs an explanatory approach with a quantitative method. Secondary time-series data were obtained from the Central Bureau of Statistics, the Ministry of Agriculture, and Bank Indonesia. The analysis uses the Ordinary Least Squares (OLS) method with a multiple linear regression model. The results indicate that simultaneously, export price, sugarcane production, sugarcane plantation area, and inflation rate significantly affect the export volume of Indonesian cane molasses. Partially, export price and inflation rate do not have a significant effect, whereas sugarcane production and plantation area positively and significantly influence the export volume. Recommendations include allocating resources for export-supporting infrastructure development, providing high-quality superior seedlings, improving agricultural infrastructure in sugarcane production centers, identifying and designating Sugarcane Development Areas (KPT) in potential regions, and implementing capacity-building programs to enhance the structural competitiveness of the molasses industry.